Recent Trends on the Mechanical Properties of Additive Manufacturing - A. García-Collado; R. Dorado-Vicente; Pablo E. Romero; Munish Kumar Gupta (Applied Sciences, 2023)
Additive Manufacturing (AM), also known as “three-dimensional printing”, has experienced significant advancements in recent years, including improvements in the mechanical properties of printed objects [...]